Pro-environmental norms and subjective well-being: Panel evidence from the UK - Martin Binder; Ann-Kathrin Blankenberg; Heinz Welsch (University of Oldenburg, Department of Economics, 2019)
Tying in with a small number of studies on green norms, identity and subjective well-being, this paper studies the relationship between holding a green self-image and life satisfaction in the UK. Focusing on (sub-national) regions as the unit of reference, we investigate if and how the individual-level greenness-satisfaction relationship varies with measures of the prevalence and distribution (disparity) of greenness at the regional level, taking these measures as indicators of a green social norm. Two key findings emerge from our analysis. First, life satisfaction is negatively related to the regional-level mean (prevalence) and positively related to the regional-level diversity of greenness, while being unrelated to the degree of polarization of greenness. Taking the prevalence as a direct and diversity as an inverse measure of the validity of a greenness norm, these results are consistent with the idea that the norm is experienced (by greens) as a standard of reference in the process of green status competition or (by non-greens) as a source of social pressure. Second, the well-being benefits from holding a greener self-image are unrelated to the prevalence and diversity of greenness, but positively related to the polarization of greenness for those either very green or not green at all. This is consistent with the idea that green self-image yields well-being benefits through identity, that is, by identifying with the own group and differentiating oneself from other groups - a possibility that relies on sufficiently large differentiation/polarization of groups. We discuss differences between these results and previous findings based on measures of nation-wide prevalence and disparity of greenness.
Keywords: I31; Q51; Q58; Z13; 330; subjective well-being; norms; green behavior; green self-image; fractionalization; polarization